PENGEMBANGAN DAN IMPLEMENTASI PANDUAN MENDESAIN PEMBELAJARAN DARING DENGAN PLATFORM SEDERHANA UNTUK GURU-GURU - Karina Almira Devitama; Eveline Siregar; Kunto Imbar Nursetyo (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
This research is a development research that aims to facilitate teachers to be able to design online learning at this time, by utilizing certain application platforms that suit their learning needs. Through this research, a Digital Guide is produced that can be used by teachers, so that in carrying out online learning or learning from home (BDR) for their students, they will be helped in using a platform that is simple and easy, but can create fun and meaningful learning. In this product development process, the Derek Rowntree development model is used, which consists of three main stages, namely 1) planning, 2) writing preparation, 3) writing and editing. At the writing and editing stage, after the product prototype is produced, expert review is carried out by material experts, media experts, and learning design experts. After experiencing improvement, the product is tested on users in a training which is designed for teachers at Tenjo Village, Bogor. The training is held in order to execute community service of Educational Technology Master Program UNJ. The test results indicated that the product is feasible to use and is very good at facilitating teachers who will design online learning, as well as selecting and using certain appropriate application platforms.